Method for preparing negative electrode active material, negative electrode active material, negative electrode containing the same, and secondary battery including the negative electrode

By mixing the carbonaceous core with asphalt and performing two heat treatments to form a carbon coating on a smooth surface, the problem of reducing negative electrode adhesion caused by large pores of carbonaceous materials is solved, and higher negative electrode adhesion and battery life characteristics are achieved.

CN114556625BActive Publication Date: 2025-04-08LG ENERGY SOLUTION LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080071962.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-28
Filing Date
2020-10-23
Publication Date
2025-04-08
Estimated Expiration
2040-10-23

AI Technical Summary

Technical Problem

In the prior art, multiple large pores of the carbonaceous material cause a decrease in the adhesion area between the negative electrode active material and the adhesive, reducing the adhesion force of the negative electrode and the life characteristics of the battery.

Method used

By mixing the carbonaceous core with asphalt and performing two heat treatments, a carbon coating with a relatively smooth surface is formed, thereby reducing the total pore volume of the negative electrode active material and improving adhesion.

Benefits of technology

The adhesion between the negative electrode active material and the adhesive is enhanced, and the adhesion of the negative electrode and the life characteristics of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003595746980000141
    Figure BDA0003595746980000141
Patent Text Reader

Abstract

The present invention relates to: a method for preparing a negative electrode active material, the method comprising the steps of: forming composite particles by mixing a carbonaceous core and asphalt and performing a first heat treatment, and mixing the composite particles and asphalt and performing a second heat treatment; a negative electrode active material; a negative electrode; and a secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority to Korean Patent Application No. 10-2019-0134845, filed on October 28, 2019, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0004] The present invention relates to: a method for manufacturing a negative electrode active material, the method comprising the steps of: mixing a carbonaceous core and asphalt and performing a first heat treatment to form composite particles, and mixing the composite particles and asphalt and performing a second heat treatment; a negative electrode active material; a negative electrode; and a secondary battery. Background Art

[0005] Due to the rapid increase in the use of fossil fuels, the need for the use of alternative energy or clean energy has increased, and as part of this trend, power generation and storage using electrochemical reactions are the most active research areas.

[0006] At present, a typical example of an electrochemical device using electrochemical energy can be a secondary battery, and there is a trend that its use field is increasingly expanding. In recent years, with the increase in the technological development and demand of portable devices such as portable computers, mobile phones and cameras, the demand for secondary batteries as energy sources has increased significantly. Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte and a separator. The negative electrode may include a negative electrode active material in which lithium ions from the positive electrode are embedded and deintercalated, and a binder that imparts adhesion so that the negative electrode active material is not deintercalated from the negative electrode. Among them, as an adhesive, styrene-butadiene rubber (SBR) is mainly used. SBR is a point-type adhesive, and is used to impart adhesion (negative electrode adhesion) between negative electrode active materials and / or between negative electrode active materials and current collectors.

[0007] On the other hand, carbonaceous materials such as graphite can be used as negative electrode active material. However, because carbonaceous material has multiple macropores formed on its surface, the adhesion area between SBR and carbonaceous material is reduced, so there is the restriction that the adhesion imparting ability of SBR is reduced. In order to solve this problem, there is a method, which forms a functional group including oxygen etc. on the surface of carbonaceous material, but this reduces the capacity of carbonaceous material.

[0008] Therefore, the present invention proposes a novel method for improving the adhesion of a negative electrode by reducing the plurality of macropores existing on the surface of a carbonaceous material. Summary of the invention

[0009] Technical issues

[0010] One aspect of the present invention provides a method of manufacturing a negative electrode active material and a negative electrode active material that can improve negative electrode adhesion.

[0011] Another aspect of the present invention provides a negative electrode and a secondary battery including the negative electrode active material.

[0012] Technical Solution

[0013] According to one aspect of the present invention, there is provided a method for manufacturing a negative electrode active material, the method comprising the steps of: mixing a carbonaceous core and a pitch and performing a first heat treatment to form composite particles; and mixing the composite particles and the pitch and performing a second heat treatment.

[0014] According to another aspect of the present invention, there is provided a negative electrode active material comprising a carbonaceous core and a carbon coating layer, and having a 3 / g to 0.010cm 3 / g total pore volume.

[0015] According to another aspect of the present invention, a negative electrode including the negative electrode active material is provided.

[0016] According to another aspect of the present invention, a secondary battery including a negative electrode is provided.

[0017] Beneficial Effects

[0018] According to the present invention, since a carbon coating having a smooth surface can be provided on a carbonaceous core, the total pore volume of the negative electrode active material can be reduced. Therefore, the adhesion between the negative electrode active material and the binder can be enhanced, thereby improving the negative electrode adhesion and the life characteristics of the battery. DETAILED DESCRIPTION

[0019] Hereinafter, the present invention will be described in more detail to enable a clearer understanding of the present invention.

[0020] It should be understood that the terms or words used in the present disclosure and claims should not be interpreted as having the meanings generally used or defined in dictionaries, but should be interpreted consistently with the technical scope of the present invention based on the concept that the inventor can appropriately define the terms to interpret the principle of the present invention at its best method.

[0021] The terminology used herein is for the purpose of describing particular exemplary embodiments only and is not intended to be limiting of the present invention.Unless the context clearly indicates otherwise, singular form terms may include plural forms.

[0022] It should also be understood that when used in this specification, the terms "includes," "comprising," or "having" indicate the presence of stated features, quantities, steps, elements, or a combination thereof, but do not exclude the presence or addition of one or more other features, quantities, steps, elements, or a combination thereof.

[0023] In this manual, the expression "D 50 " can be defined as the particle size at which the cumulative volume is 50% in the particle size distribution curve (particle size distribution curve). For example, D 50 This can be measured using laser diffraction, which is able to measure particle sizes from the submicron range to the several millimeters range, thereby obtaining highly reproducible and high-resolution results.

[0024] The Brunauer-Emmett-Teller (BET) specific surface area herein can be measured by a BELSORP-mini II apparatus (Bell Japan Inc.).

[0025] The total pore volume herein can be measured from a BET graph by using a BELSORP-mini II apparatus (Bell Japan Inc.).

[0026] <Method for producing negative electrode active material>

[0027] According to one embodiment of the present invention, there is provided a method of manufacturing a negative electrode active material, the method comprising the steps of: mixing a carbonaceous core and a pitch and performing a first heat treatment to form composite particles; and mixing the composite particles and the pitch and performing a second heat treatment.

[0028] (1) Formation of composite particles

[0029] The step of forming the composite particles may include mixing the carbonaceous core and the pitch and subjecting them to a first heat treatment.

[0030] The carbonaceous core may have an average particle size (D50) of 7 to 25 μm, specifically 8 to 23 μm, and more specifically 14 to 22 μm. When the above range is satisfied, aggregation of particles during asphalt coating may be minimized.

[0031] The carbonaceous core may include at least one selected from natural graphite, artificial graphite, and mesocarbon microbeads (MCMB).

[0032] The carbonaceous core may include secondary particles in which a carbonaceous matrix and a plurality of natural graphite particles are assembled with each other.

[0033] The secondary particles may be spherical. Specifically, the plurality of natural graphites contained in the secondary particles may be formed by modifying flaky natural graphite. Specifically, the plurality of natural graphites may be formed by agglomeration of flaky natural graphite, and more specifically, the natural graphites may be combined with each other by curling of flaky natural graphite, so that the secondary particles may have a spherical shape or a nearly spherical shape.

[0034] The secondary particles may have a sphericity of 0.73 to 0.97, particularly 0.83 to 0.96, and more particularly 0.92 to 0.95. In the case of satisfying the above range, a high-density negative electrode can be prepared, and has the effect of improving the negative electrode adhesion (the force to prevent the negative electrode active material from peeling off the negative electrode). Sphericity can be measured by a digital image analysis method (e.g., using the device name Morphologi4 (Malvern Ltd.)) by capturing a 2D image of a 3D particle.

[0035] The carbonaceous matrix may be used to maintain a state where a plurality of natural graphites are combined. The carbonaceous matrix may include amorphous carbon.

[0036] The method for manufacturing a negative electrode active material of the present invention may further include preparing a carbonaceous core. The preparation of the carbonaceous core may include mixing a plurality of flake natural graphites and pitch, and then spheroidizing the resulting mixture to form a carbonaceous core containing secondary particles.

[0037] The spheroidization process may be performed in a manner in which flake natural graphite is repeatedly folded or assembled by controlling a rotor speed or time in an apparatus such as a grinder.

[0038] The preparation of the carbonaceous core may also include removing the internal pores of the particles formed by mixing a plurality of flaky natural graphites and asphalt, and then spheroidizing the mixture. As a method for removing the internal pores of the particles, a method for filling the internal pores with asphalt, a cold isostatic pressing (CIP) method, etc. may be performed. Therefore, the pore volume of the prepared secondary particles may be at a low level. In addition, the specific surface area of ​​the negative electrode active material may be controlled by removing the internal pores, so the side reactions of the electrolyte may be reduced.

[0039] The pitch mixed with the carbonaceous core may be either petroleum-based pitch or coal-based pitch.

[0040] In the step of forming the composite particles, the weight ratio of the carbonaceous core to the pitch may be in the range of 1:0.010 to 1:0.056, particularly in the range of 1:0.040 to 1:0.056, and more particularly in the range of 1:0.045 to 1:0.056. In the case of satisfying the above range, the interface resistance is low enough to improve the fast charging performance of the battery and maintain the capacity of the negative electrode active material at a high level, and when the negative electrode is wound, the rapid increase in specific surface area can be suppressed, thereby improving the initial efficiency and high temperature storage performance of the battery.

[0041] The first heat treatment may be performed at a temperature of 1,000° C. to 1,400° C., particularly 1,050° C. to 1,350° C., and more particularly 1,100° C. to 1,300° C. The first carbon coating layer may be formed on the carbonaceous core by the first heat treatment. When the above temperature range is satisfied, the amount of hydrogen in the first carbon coating layer is suppressed, and thus the reaction of lithium ions and hydrogen may be reduced.

[0042] (2) Mixing the composite particles and asphalt and performing a second heat treatment

[0043] In the step of mixing the composite particles and the asphalt and performing the second heat treatment, the weight ratio of the composite particles and the asphalt can be in the range of 1:0.010 to 1:0.052, particularly in the range of 1:0.035 to 1:0.052, and more particularly in the range of 1:0.045 to 1:0.052. When the above range is met, the interface resistance is low enough to improve the fast charging performance of the battery and maintain the capacity of the negative electrode active material at a high level, and when the negative electrode is wound, the rapid increase in specific surface area can be suppressed, thereby improving the initial efficiency and high temperature storage performance of the battery.

[0044] The second heat treatment may be performed at a temperature of 1,000° C. to 1,400° C., particularly 1,050° C. to 1,350° C., and more particularly 1,100° C. to 1,300° C. The second carbon coating layer may be formed on the first carbon coating layer by the second heat treatment. When the above temperature range is satisfied, the amount of hydrogen in the second carbon coating layer is suppressed, and thus the reaction of lithium ions and hydrogen may be reduced.

[0045] In the case of the related art, in the case of a carbonaceous core in which a carbon coating is not formed and in which a carbon coating is formed only in a single layer on the surface by a single heat treatment process, the pores inevitably present in the core are not fully filled (the total pore volume corresponds to a high level). In the case of a large number of pores, there is a limitation in that the contact area between a point-type adhesive such as SBR and a carbonaceous core (or a carbonaceous core in which a carbon coating is formed only in a single layer by a single heat treatment process) is reduced, and thus the negative electrode adhesion is reduced.

[0046] On the other hand, in the present invention, the pores of the carbonaceous core can be fully filled by mixing and heat treating the asphalt twice, and a carbon coating with a relatively smooth surface can be formed on the carbonaceous core (the total pore volume corresponds to a low level). Therefore, since the contact area between the point-type adhesive such as SBR and the carbonaceous core can be ensured, the negative electrode adhesion can be improved.

[0047] <Negative Electrode Active Material>

[0048] The negative active material according to another embodiment of the present invention may include a carbonaceous core and a carbon coating layer, and may have a thickness of 0.003 cm 3 / g to 0.010cm 3 Here, since the carbonaceous core is the same as the carbonaceous core introduced in the above method of manufacturing a negative electrode active material, the description thereof will be omitted.

[0049] The carbon coating layer may be disposed on the carbonaceous core, and specifically, the carbon coating layer may cover at least a portion of a surface of the carbonaceous core.

[0050] The carbon coating may include amorphous carbon, and in particular, may be formed of amorphous carbon.

[0051] The carbon coating layer can be formed by performing "mixing the carbonaceous core and the pitch and performing the first heat treatment to form composite particles, and mixing the composite particles and the pitch and then second heat treating the resulting mixture" described in the above embodiment.

[0052] The negative electrode active material may have a 0.003 cm 3 / g to 0.010cm 3 / g, especially 0.0035cm 3 / g to 0.0090cm 3 / g, especially 0.0035cm 3 / g to 0.0045cm 3 / g of total pore volume. If the total pore volume is less than 0.003cm 3 / g, the ionic conductivity is reduced due to the limited contact area between the electrolyte and the negative electrode active material, which is not conducive to high-rate charging and discharging of the battery. If the total pore volume is greater than 0.010 cm 3 / g, the adhesion between the negative electrode active material and the binder is reduced, so the negative electrode adhesion is generally reduced and the battery life characteristics are reduced. 3 / g to 0.010cm 3 The pore volume of 2.547 W / g corresponds to the derived numerical range because the pores on the carbonaceous core can be effectively filled by coating the pitch twice.

[0053] The negative electrode active material may have a 0.5 m2 / g to 2.0m 2 / g, especially 1.0m 2 / g to 1.9m 2 / g, more particularly 1.0m 2 / g to 1.4m 2 When the above range is satisfied, the adhesion between the negative electrode active material and the binder is improved, so the negative electrode adhesion and the life characteristics of the battery can be improved.

[0054] <Negative electrode>

[0055] A negative electrode according to still another embodiment of the present invention may include the negative electrode active material of the above-described embodiment.

[0056] Specifically, the negative electrode may include a negative electrode active material layer, and more specifically, may include a current collector and a negative electrode active material layer.

[0057] The current collector is not particularly limited as long as it has conductivity without causing adverse chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. Specifically, transition metals such as copper and nickel that adsorb carbon well can be used as current collectors. The current collector may have a thickness of 6 μm to 20 μm, but the thickness of the current collector is not limited thereto.

[0058] The negative electrode active material layer may be disposed on the current collector. The negative electrode active material layer may be disposed on at least one surface of the current collector, and specifically on one surface or both surfaces thereof.

[0059] The negative electrode active material layer may contain a negative electrode active material, and in this case, the negative electrode active material may be the negative electrode active material of the above-described embodiment.

[0060] The negative electrode may include at least one of a binder and a conductive material.

[0061] The adhesive may include at least one selected from the following: polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials whose hydrogen is replaced by lithium (Li), sodium (Na) or calcium (Ca), or may include various copolymers thereof.

[0062] The conductive material is not particularly limited as long as it has conductivity without causing adverse chemical changes in the battery, and conductive materials such as graphite, such as natural graphite and artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers or metal fibers; conductive tubes, such as carbon nanotubes; carbon fluoride; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives can be used.

[0063] <Secondary Battery>

[0064] A secondary battery according to still another embodiment of the present invention may include a negative electrode, which is the same as the negative electrode of the above-described embodiment.

[0065] Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator disposed between the negative electrode and the positive electrode, and an electrolyte, wherein the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described above, its detailed description will be omitted.

[0066] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including a positive electrode active material.

[0067] In the positive electrode, the positive electrode current collector is not particularly limited as long as it has conductivity without causing adverse chemical changes in the battery, and, for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. Moreover, the positive electrode current collector can generally have a thickness of 3 μm to 500 μm, and can include a surface having fine concavoconvexity to improve adhesion with the positive electrode active material. For example, the positive electrode current collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0068] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may include: a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or a compound replaced by one or more transition metals; a lithium iron oxide such as LiFe3O4; a lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, V2O5 and Cu2V2O7; nickel (Ni)-site lithium nickel oxide, composed of the chemical formula LiNi 1-c2 M c2O2 (wherein M is at least one selected from the group consisting of cobalt (Co), manganese (Mn), aluminum (Al), copper (Cu), iron (Fe), magnesium (Mg), boron (B) and gallium (Ga), and c2 satisfies 0.01≤c2≤0.3); lithium manganese composite oxide, represented by the chemical formula LiMn 2-c3 M c3 O2 (wherein M is at least one selected from the following: Co, Ni, Fe, chromium (Cr), zinc (Zn) and tantalum (Ta), and c3 satisfies 0.01≤c3≤0.1) or Li2Mn3MO8 (wherein M is at least one selected from the following: Fe, Co, Ni, Cu and Zn); and LiMn2O4, a portion of which Li is replaced by alkaline earth metal ions, but the positive electrode active material is not limited thereto. The positive electrode can be Li metal.

[0069] The positive electrode active material layer may include a positive electrode conductive material and a positive electrode binder as well as the positive electrode active material described above.

[0070] In this case, the positive electrode conductive material is used to provide conductivity to the electrode, wherein any conductive material can be used without particular limitation as long as it has electronic conductivity and does not cause adverse chemical changes in the battery. Specific examples of the conductive material may be: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; powder or fiber of a metal, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof may be used.

[0071] Moreover, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples of the binder can be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof can be used.

[0072] The separator separates the negative electrode from the positive electrode and provides a path for the movement of lithium ions, wherein any separator can be used as a separator without particular limitation, as long as it is generally used for secondary batteries, and in particular, a separator having high moisture retention capacity for electrolytes and low resistance to the transfer of electrolyte ions can be used. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure having more than two layers thereof. Moreover, a typical porous nonwoven fabric can be used, for example, a nonwoven fabric formed by high melting point glass fiber or polyethylene terephthalate fiber. In addition, a coated separator comprising a ceramic component or a polymer component can be used to ensure heat resistance or mechanical strength, and a separator having a monolayer or multilayer structure can be selectively used.

[0073] The electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that may be used to prepare a lithium secondary battery, but is not limited thereto.

[0074] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0075] For example, as the nonaqueous organic solvent, aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate and ethyl propionate can be used.

[0076] Especially, ethylene carbonate and propylene carbonate, as cyclic carbonate in carbonate organic solvent, dissociate lithium salt well in electrolyte due to high dielectric constant as high viscosity organic solvent, therefore, can preferably use cyclic carbonate.Because when cyclic carbonate and low viscosity low dielectric constant straight chain carbonate such as dimethyl carbonate and diethyl carbonate are mixed with appropriate ratio, can prepare electrolyte with high conductivity, therefore can more preferably use cyclic carbonate.

[0077] The lithium salt can be used as the metal salt, and the lithium salt is a substance that is easily soluble in a non-aqueous electrolyte, wherein, for example, at least one selected from the following can be used as the anion of the lithium salt: F - , Cl - ,I- 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .

[0078] For the purpose of improving the life characteristics of the battery, preventing the battery capacity from decreasing and improving the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, the electrolyte may also contain at least one additive, such as a halogenated alkylene carbonate compound, such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, (condensed) glycol dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0079] According to another embodiment of the present invention, a battery module including a secondary battery as a unit cell and a battery pack including the battery module are provided. Since the battery module and the battery pack include secondary batteries having high capacity, high rate performance and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium to large devices selected from the following: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0080] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are only provided to illustrate the present invention, and various modifications and changes can be made within the scope and technical spirit of the present invention, and such modifications and changes are clearly included in the appended claims.

[0081] Examples and Comparative Examples

[0082] Example 1: Preparation of negative electrode active material

[0083] The flake natural graphite (D 50 :250nm) and asphalt, and then spheroidized to prepare secondary particles (D 50 : 16 μm, sphericity: 0.93), and the prepared secondary particles were used as carbonaceous cores.

[0084] The carbonaceous core and the pitch were mixed at a weight ratio of 1:0.049 and then stirred with a mixer. Then, the mixture was heat-treated at 1,200° C. for 8 hours to prepare composite particles.

[0085] The composite particles and the pitch were mixed at a weight ratio of 1:0.047 and then stirred with a mixer. Then, the mixture was heat-treated at 1,300° C. for 9 hours to manufacture a negative electrode active material.

[0086] Example 2: Preparation of negative electrode active material

[0087] The flake natural graphite (D 50 :250nm) and asphalt, and then spheroidized to prepare secondary particles (D 50 : 16 μm, sphericity: 0.93), and the prepared secondary particles were used as carbonaceous cores.

[0088] The carbonaceous core and the pitch were mixed at a weight ratio of 1:0.043 and then stirred with a mixer. Then, the mixture was heat-treated at 1,250° C. for 7 hours to prepare composite particles.

[0089] The composite particles and the pitch were mixed at a weight ratio of 1:0.042 and then stirred with a mixer. The mixture was then heat-treated at 1,300° C. for 9 hours to produce a negative electrode active material.

[0090] Example 3: Preparation of negative electrode active material

[0091] The flake natural graphite (D 50 :250nm) and asphalt, and then spheroidized to prepare secondary particles (D 50 : 16 μm, sphericity: 0.93), and the prepared secondary particles were used as carbonaceous cores.

[0092] The carbonaceous core and the pitch were mixed at a weight ratio of 1:0.032 and then stirred with a mixer. Then, the mixture was heat-treated at 1,200° C. for 7 hours to prepare composite particles.

[0093] The composite particles and the pitch were mixed at a weight ratio of 1:0.031 and then stirred with a mixer. Then, the mixture was heat-treated at 1,300° C. for 9 hours to manufacture a negative electrode active material.

[0094] Example 4: Preparation of negative electrode active material

[0095] The flake natural graphite (D 50 :250nm) and asphalt, and then spheroidized to prepare secondary particles (D 50 : 11 μm, sphericity: 0.90), and the prepared secondary particles were used as carbonaceous cores.

[0096] The carbonaceous core and the pitch were mixed at a weight ratio of 1:0.043 and then stirred with a mixer. Then, the mixture was heat-treated at 1,300° C. for 6 hours to prepare composite particles.

[0097] The composite particles and the pitch were mixed at a weight ratio of 1:0.042 and then stirred with a mixer. The mixture was then heat-treated at 1,300° C. for 8 hours to produce a negative electrode active material.

[0098] Comparative Example 1: Preparation of negative electrode active material

[0099] The carbonaceous core and the pitch used in Example 1 were mixed at a weight ratio of 1:0.064 and then stirred with a mixer. Then, the mixture was heat-treated at 1,300° C. for 10 hours to prepare composite particles.

[0100] [Table 1]

[0101]

[0102] The BET specific surface area was measured by a BELSORP-mini II apparatus (Bell Japan Inc.) The total pore volume was measured from a BET graph by using a BELSORP-mini II apparatus (Bell Japan Inc.).

[0103] Experimental Example 1: Evaluation of negative electrode adhesion

[0104] A negative electrode was prepared by using each of the negative electrode active materials of Examples 1 to 4 and Comparative Example 1 as follows.

[0105] Specifically, each negative electrode active material, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 96.6:1:1.3:1.1, and water was added thereto to prepare a negative electrode slurry. The negative electrode slurry was coated on a copper foil (current collector) and then vacuum dried at 130°C for 10 hours to produce a negative electrode (1.4875 cm 2 The loading capacity of the prepared negative electrode is 3.61 mAh / cm 2 .

[0106] The negative electrode was punched out at 20 mm×150 mm, fixed to the center of a 25 mm×75 mm glass slide using tape, and then the 90° peel strength was measured while the current collector was peeled using UTM. Five or more peel strengths were measured, and the average value thereof was used for evaluation, and the results are shown in Table 2.

[0107] [Table 2]

[0108] Negative electrode adhesion (gf / 10mm) Example 1 30 Example 2 27 Example 3 25 Example 4 18 Comparative Example 1 14

Claims

1. A method for manufacturing a negative electrode active material, the method comprising the following steps: mixing a carbonaceous core and pitch and subjecting the mixture to a first heat treatment to form composite particles, wherein a first carbon coating is formed on the carbonaceous core; and mixing the composite particles and pitch and performing a second heat treatment to form a second carbon coating layer, wherein the second carbon coating layer is formed on the first carbon coating layer, The negative electrode active material has a 0.003 cm 3 / g to 0.010cm 3 Total pore volume / g, wherein the carbonaceous core comprises at least one selected from the group consisting of natural graphite, artificial graphite and mesocarbon microbeads (MCMB), The carbonaceous core includes secondary particles in which a carbonaceous matrix and a plurality of natural graphite particles are assembled with each other. 2 . The method according to claim 1 , wherein the first heat treatment is performed at a temperature of 1,000° C. to 1,400° C. 3 . The method according to claim 1 , wherein the second heat treatment is performed at a temperature of 1,000° C. to 1,400° C.

4. The method according to claim 1, wherein: In the step of forming composite particles, a weight ratio of the carbonaceous core to the pitch is 1:0.010 to 1:0.

056.

5. The method according to claim 1, wherein: In the step of mixing the composite particles and asphalt and performing a second heat treatment, a weight ratio of the composite particles to the asphalt is 1:0.010 to 1:0.

052.

6. The method according to claim 1, wherein the carbonaceous core has an average particle size D of 7 μm to 25 μm. 50 .

7. The method according to claim 1, further comprising the step of preparing the carbonaceous core, The step of preparing the carbonaceous core comprises: A plurality of flake natural graphite and pitch are mixed, and the resulting mixture is then spheroidized.

8. The method according to claim 7, further comprising the step of removing internal pores after the spheroidizing process.

9. A negative electrode active material, comprising a carbonaceous core, a first carbon coating layer and a second carbon coating layer, and having a thickness of 0.003 cm 3 / g to 0.010cm 3 Total pore volume / g, wherein the first carbon coating is formed on the carbonaceous core, and the second carbon coating is formed on the first carbon coating, wherein the carbonaceous core comprises at least one selected from the group consisting of natural graphite, artificial graphite and mesocarbon microbeads (MCMB), The carbonaceous core includes secondary particles in which a carbonaceous matrix and a plurality of natural graphite particles are assembled with each other.

10. The negative electrode active material according to claim 9, wherein the negative electrode active material has a 2 / g to 2.0m 2 / g BET specific surface area. 11 . The negative electrode active material according to claim 9 , wherein the carbonaceous core has an average particle diameter D50 of 7 μm to 25 μm. 12 . A negative electrode comprising the negative electrode active material according to claim 9 . 13 . A secondary battery comprising the negative electrode according to claim 12 .

Citation Information

Patent Citations

  • Screw compressor

    KR1020190134845A

  • Negative electrode active material for rechargeable lithium battery, method for preparing the same and rechargeable lithium battery including the same

    CN104218227A

  • Anode active material for lithium secondary battery and anode for lithium secondary battery including same

    EP3297073A1

  • Negative electrode active material for lithium secondary battery, negative electrode using the same, and manufacturing method

    JP2008186732A

  • Negative electrode active material for rechargeable lithium battery, method for preparing the same and rechargeable lithium battery including the same

    KR1020140140323A